All the bright places - Niven, Jennifer 1968- (Borzoi Book, 2015)
"Told in alternating voices, when Theodore Finch and Violet Markey meet on the ledge of the bell tower at school...both teetering on the edge...it's the beginning of an unlikely relationship, a journey to discover the "natural wonders" of the state of Indiana, and two teens' desperate desire to heal and save one another"